Gait analysis in hip viscosupplementation for osteoarthritis: a case report - L. Di Lorenzo (Reumatismo, 2013)
Hip is a site very commonly affected by osteoarthritis and the intra-articular administration of hyaluronic acid in the management of osteoarthritic pain is increasingly used. However, the debate about its usefulness is still ongoing, as not all results of clinical trials confirm its effectiveness. In order to achieve the best outcome, clinical assessment and treatment choices should be based on subjective outcome, pathological and mechanical findings that should be integrated with qualitative analysis of human movement. After viscosupplementation, clinical trials often evaluate as endpoint subjective outcomes (i.e. pain visual analogic scale) and static imaging such as radiographs and magnetic resonance imaging. In our clinical practice we use gait analysis as part of rehabilitation protocol to measure performance, enhancement and changes of several biomechanical factors. Taking advantage of available resources (BTS Bioengineering gait analysis Elite System) we studied a patient’s gait after ultrasound guided hip injections for viscosupplementation. He showed an early clinical and biomechanical improvement during walking after a single intra articular injection of hyaluronic acid. Gait analysis parameters obtained suggest that the pre-treatment slower speed may be caused by antalgic walking patterns, the need for pain control and muscle weakness. After hip viscosupplementation, the joint displayed different temporal, kinetic and kinematic parameters associated with improved pain patterns.